Efficacy of transcranial magnetic stimulation treatment in reducing neuropsychiatric symptomatology after traumatic brain injury - Riccitelli, Gianna Carla; Borgonovo, Riccardo; Villa, Mariasole; Pravatà, Emanuele; Kaelin-Lang, Alain (Frontiers in Neurology, 2024)
Background: Neuropsychiatric disorders are highly disabling in traumatic brain injury (TBI) patients and often psychopharmacological therapy is not enough to limit its detrimental effects. Repetitive transcranial magnetic stimulation (rTMS) treatment is growing in the field of neurology and psychiatry, with potential in treating psychiatric disorders. Objective: This study explores the efficacy of a novel, dual-site sequential rTMS protocol designed to address neuropsychiatric symptoms in a TBI patient refractory to conventional medication. Methods: A 34-year-old woman with severe head trauma and complex psychopathology underwent 20 daily sessions of focal-coil inhibitory (1Hz) and excitatory (10Hz) rTMS on right and left dorsolateral prefrontal cortex guided by a Neuronavigation system. Psychiatric and neurocognitive assessment were performed at baseline, two, four, and eight weeks from the beginning of rTMS treatment. Results: After 2 weeks of treatment, the patient showed decreased impulsivity and obsessive-compulsive symptoms, improved attention, and faster processing speed. After 4 weeks, impulsivity further declined without other significant changes. A persistent positive effect, including enhanced positive emotions, was evident after 8 weeks. Discussion: These findings suggest that guided, alternating neurostimulation of the DLPFC may modulate the activity within cortico-striato-thalamo-cortical circuits providing a promising alternative for managing neuropsychiatric symptoms in TBI patients resistant to traditional treatments.